THE EFFECT OF QUALITY OF SERVICE, CUSTOMER EXPERIENCE, AND PROMOTION ON CUSTOMER SATISFACTION (A Study at BSH Coffee in Denpasar City) - Putu Bagus Suryanatha; I Gst. Ngr. Jaya Agung Widagda K (Adisam Publisher, 2026)
This study aims to examine the effects of quality of service, customer experience, and promotion on customer satisfaction using the Expectation Confirmation Theory as the theoretical foundation. The theory posits that customer satisfaction is formed through the alignment between customers’ initial expectations and the actual performance of the service received. A quantitative research approach was employed, with data collected through questionnaires distributed to active customers of BSH Coffee in Denpasar City. The findings indicate that quality of service has a positive and significant effect on customer satisfaction, suggesting that higher service quality leads to greater customer satisfaction. Customer experience also demonstrates a significant positive influence, as favorable experiences enhance customers’ perceptions of the value provided by the service. Furthermore, promotion significantly affects customer satisfaction by shaping customers’ initial expectations before consuming the products or services offered. Simultaneously, the three independent variables were found to contribute significantly to customer satisfaction. These findings highlight the importance for businesses to continuously improve service quality, create memorable customer experiences, and develop effective promotional strategies to meet and exceed customer expectations in accordance with the principles of Expectation Confirmation Theory.